Srednji detel Dendrocopos - Košir, Martin (Acrocephalus, 1998)
Male on 29th January 1998 near Pleterje monastery
Keywords: Middle spotted Woodpecker; opazovanje; ornithology; ornitologija; Pleterje; Slovenia; srednji detel